Regional heterogeneity of preferences and intergovernmental transfers - Raúl A. Ponce Rodríguez; Benito Alan Ponce Rodríguez (Economies, 2021)
We develop a model with optimal shares of intergovernmental transfers, and we apply a simulation analysis of our model for the case of Mexico. The main outcomes of this paper are as follows: First, we provide optimal shares of intergovernmental funds to be allocated in each state considering the regional distribution of the benefits of local public spending in Mexico. Second, our analysis shows that the regional heterogeneity of preferences across regions should be an important determinant of federal funds allocated to state governments. Third, the current system of finance relies on a tax revenue sharing accord that emphasizes nationwide tax collection issues as the main determinants of intergovernmental transfers and local spending. Our analysis provides a contrast between how fiscal policy is conducted, and feasible choices of policy reform. Fourth, our analysis of simulation identifies winners and losers from policy reform, and so our analysis contributes to a better understanding of the advantages and shortcomings of the current policy of intergovernmental transfers, providing feasible ways to improve the outcomes of subnational government spending.
Keywords: 330; intergovernmental transfers; fiscal federalism; income distribution; efficiency; heterogeneity of preferences